Senior Citizens Learning On-Line; Needs And Expectations - Escuder-Mollon, Pillar; Lipphardt, Anne-Marie (INTED2017 Proceedings, 2017)
Educational institutions are increasingly offering virtual learning spaces to students to acquire competences and skills regardless of time and space. The most common configuration is the blended learning (virtual and physical teaching mixed) but it is being increasingly offered completely virtual teaching, mainly to adults in very specific subjects in specialization course, or other job-skills subjects. This kind of learning is not advised in children, neither in senior citizens as some of the competences they have to reach require a face-to-face contact and real group interaction or when social contact is one of the priorities. Even we are aware of the limitations of full virtual learning, it is necessary to acknowledge the enormous advantages it provides, increasing the access of people to education (mostly if those life in rural areas, or disabled). Furthermore, it is also worth mentioning that nowadays, because of the great extend of technology in everyday life, the virtual socialization deserves as much attention as the real life socialization. Senior students are enrolled in educational institutions mainly because of personal motivations (not because of job skills or competitiveness) and they attend to courses because they want to keep active and up-to-date, sharing the time with other classmates, enjoying and learning from this experience. This interaction is reached thanks to physical learning environments, for this reason it is not usual to offer full virtual learning spaces for senior learners. Furthermore statistically senior citizens are not so computer skilled as younger, therefore, they prefer face-to-face learning. In the EHHLSA project we analysed the expectations and interests of the senior citizens about virtual learning, and the preferred topics. We also wanted to know their preferred method for learning and if they had experience on ICT mediated education, we wanted to know their experience. From previous results and data analysis it is possible to conclude that their involvement in on-line learning is a result of a decision originated mainly from their cultural context and social environment, that is the life-long learning attitude and the use of Internet because it is a social duty. Success on the first steps on on-line learning environments is based on course topics, the skills of the facilitator, the environment and an appropriate methodology. After this barrier is overtaken, there is an increase on the involvement on on-line learning platforms. This can be seen as a virtuous circle based on senior citizens experience and with a three dimensional aspects: learn and use of technology, learn new things and topics, and enjoy being part of the virtual community. The results of this research are framed in the “European home learning service for seniors association” (http://ehlssa.odl.org/) KA2 Erasmus + Strategic partnership projec